2017
DOI: 10.1007/s00701-017-3318-6
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical versus endoscopic transsphenoidal resection for acromegaly: a systematic review of outcomes and complications

Abstract: Both endoscopic and microsurgical approaches for TSR of growth hormone-secreting adenomas are viable treatment options for patients with acromegaly, and yield similarly high rates of remission under the most current consensus criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 106 publications
3
62
0
7
Order By: Relevance
“…In patients with functional pituitary adenomas (growth hormone-secreting adenoma), Phan and coworkers ( 59 ) concluded that clinical use of the endoscopic approach conferred potential benefits, including increased remission rates with non-invasive macroadenomas, but that overall endocrine remission is comparable. Chen and coworkers ( 60 ) also concluded that both approaches yielded similar rates of remission. However, a meta-analysis comparing outcomes from endoscopic TS and microscopic TS was lacking.…”
Section: Discussionmentioning
confidence: 92%
“…In patients with functional pituitary adenomas (growth hormone-secreting adenoma), Phan and coworkers ( 59 ) concluded that clinical use of the endoscopic approach conferred potential benefits, including increased remission rates with non-invasive macroadenomas, but that overall endocrine remission is comparable. Chen and coworkers ( 60 ) also concluded that both approaches yielded similar rates of remission. However, a meta-analysis comparing outcomes from endoscopic TS and microscopic TS was lacking.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the rate of CSF leak after expanded methods is significantly higher than the rate during endoscopic approaches in which the arachnoid space is not intentionally violated. [4][5][6] A major risk factor for developing meningitis following EETS is the presence of a postoperative CSF leak. 4,7,8 The consequences from meningitis can be life-threatening 9 and carries risks of both long-term physiological and cognitive impairements [10][11][12] ; therefore, it is crucial to identify clinical features that may predispose patients to postoperative infections.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of patients with acromegaly is aimed at normalizing GH and/or IGF1 levels to ameliorate signs and symptoms of the disease 2,4,5 and reduce excess mortality [6][7][8] . Long-term biochemical control is achieved in fewer than 65% of patients following surgical resection of the tumour despite the use of novel surgical approaches [9][10][11][12][13][14][15] , and only approximately half of patients treated with medical therapy achieve control of IGF1 levels [16][17][18][19] . Radiation therapy remains an option in patients with persistently active disease, but rates of control and safety have only marginally improved with the use of stereotactic radiosurgery instead of conventional fractionated radiotherapy 20 .…”
mentioning
confidence: 99%